The impact of tropomyosins on actin filament assembly is isoform specific. Issue 4 (3rd July 2016) - Janco, Miro; Bonello, Teresa T.; Byun, Alex; Coster, Adelle C. F.; Lebhar, Helene; Dedova, Irina; Gunning, Peter W.; Böcking, Till
Abstract: Tropomyosin (Tpm) is an α helical coiled-coil dimer that forms a co-polymer along the actin filament. Tpm is involved in the regulation of actin's interaction with binding proteins as well as stabilization of the actin filament and its assembly kinetics. Recent studies show that multiple Tpm isoforms also define the functional properties of distinct actin filament populations within a cell. Subtle structural variations within well conserved Tpm isoforms are the key to their functional specificity. Therefore, we purified and characterized a comprehensive set of 8 Tpm isoforms (Tpm1.1, Tpm1.12, Tpm1.6, Tpm1.7, Tpm1.8, Tpm2.1, Tpm3.1, and Tpm4.2), using well-established actin co-sedimentation and pyrene fluorescence polymerization assays. We observed that the apparent affinity (Kd(app) ) to filamentous actin varied in all Tpm isoforms between ∼0.1–5 μM with similar values for both, skeletal and cytoskeletal actin filaments. The data did not indicate any correlation between affinity and size of Tpm molecules, however high molecular weight (HMW) isoforms Tpm1.1, Tpm1.6, Tpm1.7 and Tpm2.1, showed ∼3-fold higher cooperativity compared to low molecular weight (LMW) isoforms Tpm1.12, Tpm1.8, Tpm3.1, and Tpm4.2. The rate of actin filament elongation in the presence of Tpm2.1 increased, while all other isoforms decreased the elongation rate by 27–85 %. Our study shows that the biochemical properties of Tpm isoforms are finely tuned and depend on sequence variations in alternatively spliced regions of Tpm molecules.